Does mitigation begin at home? - Diederich, Johannes; Goeschl, Timo (Discussion paper series, 2017)
In a climate system that is indifferent about where mitigation is carried out, the logic of comparative advantages favors abatement locations in developing and rapidly industrializing countries. There is evidence, however, that citizens of industrialized countries who voluntarily fund climate mitigation activities are not indifferent about the mitigation location. In our artifactual online experiment, subjects located in a European Union member state took a dichotomous choice between a cash prize and the verified mitigation of one metric ton of CO2. The treatment condition varied the location of the mitigation activity between the European Union and developing countries. We test whether the location impacts on the probability that the mitigation activity is chosen, harnessing between- and within-subject Variation in our panel data. Our evidence shows that subjects responded to the location being made salient, but, contrary to previous concerns, were indifferent between mitigation sites in the EU or developing countries.